STUDY ON THERMAL COMFORT FACTORS IN CONVERSION-ADAPTIVE BUILDING, CASE STUDY IN SURAKARTA INDISCHE HOUSE - Noor Fitri Indah Padmasari; Agus Hariyadi (Built Environment Studies, 2023)
Traditional buildings are one type of structure that can adapt to a dynamic environment. Some functions of the building’s spaces have been changed to the new requirements, but the building's overall shape has been preserved. The purpose of this study was to examine and determine the differences in perceived thermal comfort values ​​between occupants and visitors inside the building. Using the observation method and analyzing the data through PMV-PPD and correlating with the Adaptive method in the Center for the Built Environment (CBE) Thermal Comfort Tool Website, it shows that there are differences caused by the environmental climate that do not match the PMV standard from ASHRAE. This study also has shown a difference of 18% between the PMV value of visitors to occupants, where there are past factors that influence this difference, and also a difference of 0.58 between the PMV value of Fanger and Sugini theory (comparison between general theory that is often used with the local theory that has been researched), because of Indonesians' heat tolerance. In this study, it was found that there are variables that are not needed in the adaptive method approach of naturally ventilated buildings, namely the humidity in buildings that are in tropical and humid areas. The reason for this is that the effect of moisture on the thermal sensation is insignificant, and it can be neglected.